Analysis of a bicyclist`s head injury in lateral and frontal impact using the human full-body model - Teng, T.-L.; Liang, C.-C.; Nguyen, V.-H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
Helmets reduce the frequency and severity of head and brain injuries resulting from bicycle crashes. To ensure that all bicycle helmets provide a certain level of effectiveness, helmets are required to satisfy certain standards of construction and material design before they can be sold in the market. Impact protection is the primary consideration of nearly every helmet standard. The general terms for a test for assessing impact protection involve shock absorption. A helmeted headform is dropped onto an anvil and the headform acceleration is measured. However, the test procedures of the existing standards do not properly assess the protection level of helmets against oblique impacts. To investigate bicycle helmets in a real accident scenario, this study simulated the full body of a bicyclist when free falling onto a road. This study considered the normal velocity (VN) of 5.66 m/s and tangential velocity (VT) values of 0, 5, and 10 m/s. Finite element analyses of helmet impact tests were conducted using LS-DYNA software. Moreover, the impact responses obtained using full-body and detached-headform models were compared under identical impact conditions. The analysis results obtained herein can be useful for evaluating helmet quality and guiding future developments in helmet innovation.